Facile approach for the synthesis of spherical mesoporous silica nanoparticles from sodium silicate - Hwang, Jongkook; Lee, Jin Hyung; Chun, Jinyoung (Materials Letters, 2021)
We developed a facile synthetic method for the preparation of spherical mesoporous silica nanoparticles from a sodium silicate solution. Spherical mesoporous silica with an overall size of several hundreds of nanometers was obtained through a simple sol–gel process using acetic acid and polyethylene glycol (PEG) as a pH adjuster and morphology directing agent, respectively. In this method, PEG is an essential component that affects the shape of silica particles and that leads to the formation of mesopores on silica. Additionally, the size of the mesopores could be easily controlled by changing the reaction temperature. Thus, we successfully synthesized spherical silica nanoparticles with tunable mesopores ranging from 3 to 40 nm. This synthetic method can be valuable in developing customized porous silica nanoparticles using an inexpensive silica resource.
Keywords: Gel process; Meso-pores; Reaction temperature; Silica particles; Sodium silicate; Sodium silicate solutions; Spherical mesoporous silica; Synthetic methods; Mesoporous materials; Nanoparticles; Polyethylene glycol; Sodium silicate; Sol-gel process; Spherical silica